Early and late outcome of skeletonised bilateral internal mammary arteries anastomosed to the left coronary system. Issue 2 (18th January 2005) - Bonacchi, M; Battaglia, F; Prifti, E; Leacche, M; Nathan, N S; Sani, G; Popoff, G
Abstract : Objectives: To investigate in a retrospective study the technical aspects of using the in situ bilateral internal mammary arteries (IMAs), with the right IMA (RIMA) used for revascularisation of the circumflex system, and to evaluate early and late outcome. Materials and methods: Between January 1997 and July 2003, 552 consecutive patients underwent grafting of the circumflex artery system with an in situ skeletonised RIMA routed through the transverse sinus (eventually retrocaval). Mean (SD) age was 63.8 (11) years. 331 (60%) patients underwent total arterial myocardial revascularisation. Mean follow up was 26 (9) months. Results: The success rate of skeletonised RIMA grafting to the circumflex branch was 100%. There were 19 (3.4%) in-hospital deaths. Perioperative myocardial infarction occurred in 12 (2.2%) patients. In 155 patients undergoing postoperative angiography, two had an occluded RIMA and a string-like phenomenon was seen in three RIMA and one left IMA (LIMA). Three RIMA and three LIMA had stenotic lesions. The patency rates of RIMA and LIMA were 94% and 97.4%, respectively. Strong predictors of non-functional IMA grafts were a recipient coronary artery diameter of < 1.5 mm (p  =  0.022), < 60% stenosis of the recipient coronary artery (p  =  0.015), diffuse stenotic lesions of the recipient coronary artery (p  =  0.018), and a small IMA calibre (p  =  0.0001). Cumulative actuarial survival at three years was 96.4% and event-free cumulative survival was 93.8%. Conclusions: Use of the bilateral IMAs offers the possibility of constructing various configurations, making total arterial myocardial revascularisation possible with a minimum number of arterial conduits. Use of the skeletonised RIMA through the transverse sinus and eventually retrocavally can reach most branches of the circumflex system and is associated with an excellent patency rate. Patients who received bilateral IMA grafts for left coronary system revascularisation had improved early and late outcomes and decreased risk of death, reoperation, and angioplasty.